Diseño de un modelo de gestión del conocimiento para la empresa Aglomerados Cotopaxi S.A. Para optimización del capital intelectual. - Olmos Valdez, Jenny Maricela (2020)
Currently, the administration of knowledge in organizations has broken paradigms under the business dynamics of information technology, since they allow establishing conditions for the implementation of knowledge management, based on the exploitation of the capabilities of each of the members of the organization. From an economic-financial point of view, the problem centers on the book value given by the sum of the value of its tangible assets; However, intangible resources are increasingly important to organizations, but not all are valued in financial information because they are difficult to control and measure. Therefore, the research objective is to design a knowledge management model for the company Aglomerados Cotopaxi SA, for the optimization of intangible capital management. For this, descriptive and field research was applied through of the survey which showed that knowledge reaches efficiency when activities and related resources are managed as a process, however this process is currently limited to the collection and filing of certain information but not to its dissemination